Regional differences in the developmental trajectory of lateralization of the language network. Issue 1 (3rd October 2012) - Berl, Madison M.; Mayo, Jessica; Parks, Erin N.; Rosenberger, Lisa R.; VanMeter, John; Ratner, Nan Bernstein; Vaidya, Chandan J.; Gaillard, William Davis
<x xml:space="preserve">Abstract</x> The timing and developmental factors underlying the establishment of language dominance are poorly understood. We investigated the degree of lateralization of traditional frontotemporal and modulatory prefrontal‐cerebellar regions of the distributed language network in children (n = 57) ages 4 to 12—a critical period for language consolidation. We examined the relationship between the strength of language lateralization and neuropsychological measures and task performance. The fundamental language network is established by four with ongoing maturation of language functions as evidenced by strengthening of lateralization in the traditional frontotemporal language regions; temporal regions were strongly and consistently lateralized by age seven, while frontal regions had greater variability and were less strongly lateralized through age 10. In contrast, the modulatory prefrontal‐cerebellar regions were the least strongly lateralized and degree of lateralization was not associated with age. Stronger core language skills were significantly correlated with greater right lateralization in the cerebellum. Hum Brain Mapp 35:270–284, 2014. © 2012 Wiley Periodicals, Inc.